2015
DOI: 10.1177/0884533615611858
|View full text |Cite
|
Sign up to set email alerts
|

Avulsed Nasoenteric Bridle System Magnet as an Intranasal Foreign Body

Abstract: Nasoenteric tubes provide short-term nutrition support to patients unable to take an adequate oral diet. Bridling systems may be used to secure tubes to guard against displacement. We present the first case of an avulsed magnet from a bridling system to raise awareness of this potential complication. The primary methods of securing a nasogastric tube are reviewed, and comparative assessment of the 3 main systems is presented. Diagnosis and management of nasal foreign bodies relevant to this case are reviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The artifact was eventually discovered upon a CT scan [18]. Additionally, Puricelli et al have reported the first case of an avulsed bridle magnet in the United States, arguing that although a rare complication, magnetic tip dislodgement can elicit debilitating consequences for the patient [19]. Therefore, to our knowledge, the present report represents only the second case of magnetic dislodgement from a nasal bridle in the United States.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The artifact was eventually discovered upon a CT scan [18]. Additionally, Puricelli et al have reported the first case of an avulsed bridle magnet in the United States, arguing that although a rare complication, magnetic tip dislodgement can elicit debilitating consequences for the patient [19]. Therefore, to our knowledge, the present report represents only the second case of magnetic dislodgement from a nasal bridle in the United States.…”
Section: Discussionmentioning
confidence: 63%
“…Certain anatomical observations might also contribute towards the uneventful bridle insertion. Puricelli et al posited that insertion of the bridle at the level of the nasal floor is likely to proceed unhindered, and it is pivotal to ensure that the bridle is parallel to the nasal floor upon insertion [19]. Furthermore, the pre-insertional application of a nasal decongestant is likely to diminish the turbinate dimensions, enabling smoother passage.…”
Section: Discussionmentioning
confidence: 99%
“…Dressing used to adhere tube to the cheek or neck Tube is less visually distracting Works well for small, soft tubes; including dressing close to naris adds to security and may reduce "pistoning" or movement of the tube at the naris May be at increased risk for skin breakdown 81 Need to ensure bridle clip does not place pressure on nares resulting in pressure injury [82][83][84] It could also result in internal injury if the tube gets caught or pulled on if allowed to hang from the nose Can be cost-effective as compared with tape, owing to less tube displacement with the bridle 85 Securing the neck lends extra stabilization Devices associated with reported complications such as nasal bleeding [86][87][88][89] facilities have developed policies and procedures for placing feeding tubes during the day while having the bedside RN place an OG or NG tube if enteral access is needed on evening or night shifts. 14 Placing an NG tube instead of an NE tube on "off" shifts may not be ideal, but each facility must weigh the risks vs the benefits of this practice based on the training and availability of their staff.…”
Section: Transparent Dressingmentioning
confidence: 99%
“…Inadvertent dislodgement of a small-bore feeding tube not only disrupts the delivery of important nutrition support but also increases the risk of aspiration pneumonia. 4,5,9,12,13 There may be increased exposure to radiation with each small-bore feeding tube placement if an x-ray is used to assess tube position. 14 All of these factors can contribute to increased cost and greater patient risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although adhesive tape is an inexpensive and a widely used method of securing feeding tubes, it has an associated rate of inadvertent tube dislodgement between 20% and 53%. [4][5][6][7][8][9][10][11] ICU patients who frequently experience delirium are prone to pulling out tubes and lines. Inadvertent dislodgement of a small-bore feeding tube not only disrupts the delivery of important nutrition support but also increases the risk of aspiration pneumonia.…”
Section: Introductionmentioning
confidence: 99%